Analysis of Legal Protection Regarding The Intellectual Property Rights of Electronic Book Creators in The Digital Era - Fanni Choirul Prastyowati; Andria Luhur Prakoso (The Indonesian Journal of International Clinical Legal Education, 2024)
Legal protection is a basic principle in the legal system which refers to the efforts and mechanisms used by the law to protect the rights, interests and security of certain individuals, groups or legal entities. Legal protection ensures that individuals’ basic rights and freedoms are protected from actions that could harm them. These include rights such as freedom of speech, the right to privacy, the right to justice, property rights, and more. The writing of this journal uses normative legal research methods, which is a type of research that is often used to study norms in statutory regulations that have been formulated clearly and do not have multiple interpretations. The author uses a statutory approach as the object of his research, namely Law Number 28 of 2014 (Copyright Law). The technique used is the library research method, with the aim that this research can provide detailed information about IPR protection in the digital era. Protection of Intellectual Property Rights for these objects provides incentives for individuals, companies and innovators to continue to innovate , creates, and invests in intellectual property. It also promotes healthy competition, consumer protection, and sustainable economic growth. IPR is a legal framework that grants exclusive rights to creators or rights holders over their intellectual works. The aim of IPR is to encourage innovation, creativity and economic development by providing appreciation and legal protection for these intellectual works.